(untitled) (Altre Modernità, 2025)
In Theocritus’ idyll 16 (Graces or Hiero) the previous literary tradition is widely used and it becomes also explicit term of comparison for a reflection about the value of poetry and its development over time (vv. 34-57). Theocritus, who focuses on the praise function of poetry, seems to have in mind above all choral lyric poets as Simonides, Pindar and Bacchylides. Nevertheless, he changes the way he deals with these literary models in the course of the idyll. Indeed, in the first part of the poem, where despair and condemnation are the prevailing attitudes, the topoi of the eulogistic works are precisely overturned, in order to highlight the impossibility to replicate in the contemporary age the same social factors thanks to which the traditional poetic repertoire was formed. On the contrary, in the second part of the idyll, where the narrator seems finally to find Hiero II as a possible patron to praise, the characteristic motifs of the laudatory works are used in a ‘conservative’ way. The overall outcome is not only a vivid picture of the intellectual’s condition in the Hellenistic age, but also a complex operation of closeness to and distance from the encomiastic models of the past.